Step-by-step CVD (Chemical Vapor Deposition) preparation method for improving low-temperature cyclicity of graphite cathode material

Carbon coating on graphite substrate material is solved by step-by-step CVD method, and the problem of insufficient uniformity and stability in the existing liquid phase coating technology is significantly improved, and the circulation performance of lithium batteries at low temperatures is significantly improved.

CN119461358AInactive Publication Date: 2025-02-18GANZHOU RUIFUTE TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510051831.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing liquid phase coating technology has problems such as poor uniformity, easy agglomeration after coating, asphalt, etc., which are likely to endanger physical health, excessive heating temperature of the coating kettle is too high, and there are many uncontrollable factors.

Method used

The carbon-coated deposition and growth is carried out on the surface of graphite substrate material by step-by-step CVD. By controlling the types, flow rates, temperatures, and pressures of the reaction gas, the precursor of the gas phase gradually reacts and deposits on the surface of the substrate material to form Dense and uniform cladding.

Benefits of technology

The cycle stability of the graphite negative electrode material is improved, especially the cycle capacity at low temperatures, and the obtained graphite composite negative electrode material has a capacity of more than 87.5% after 500 cycles at 0°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461358A_ABST
    Figure CN119461358A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium battery negative electrode materials, and particularly relates to a step-by-step CVD preparation method for improving the low-temperature cyclicity of a graphite negative electrode material. The preparation method comprises the following steps: firstly preparing a core layer of the graphite negative electrode material, and then preparing the carbon-coated graphite composite negative electrode material by adopting a step-by-step CVD (Chemical Vapor Deposition) method. According to the invention, a graphite substrate is used as a core layer of a negative electrode material, then a step-by-step CVD method is adopted to perform a nucleation reaction at a low speed to deposit a layer of high-compactness and uniform initial film by controlling the type, flow rate, temperature, pressure and other conditions of reaction gas, and then a layer of amorphous carbon layer is grown cyclically at a relatively high speed to prepare the negative electrode material. The distributed CVD preparation method has the characteristics of controllable growth and uniform and compact coating, can effectively improve the cycling stability of the lithium battery, and particularly improves the cycling stability of the lithium battery at a low temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium battery negative electrode materials, and specifically relates to a step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials. Background Art

[0002] At present, lithium batteries have the characteristics of high energy, long cycle, and low environmental pollution, and have been widely used in electronic products and new energy vehicles. Especially in recent years, new energy vehicles have developed rapidly, and the demand for lithium-ion batteries with higher performance indicators has been growing. Among them, liquid-phase coated graphite negative electrode material is a commonly used battery modification method. By coating graphite with asphalt and petroleum and carbonizing it, a thin film or coating is formed on the surface of the graphite to improve the various performance indicators of the battery. Chinese patent CN118619267A discloses a production process of a liquid-phase coating agent, which belongs to the field of negative electrode production technology. It is produced by catalysis and compounding of multiple raw materials to obtain the liquid-phase coating agent. The liquid-phase coating agent produced by this process has the characteristics of less capacity loss, uniform coating, and no loss of initial effect after coating. Chinese patent CN103682350B discloses the preparation and application of a lithium battery negative electrode material of asphalt liquid-phase coated modified artificial graphite. The method comprises mechanically crushing petroleum coke, mixing it with an appropriate amount of asphalt powder after grading treatment, reacting it in a medium-temperature reactor at 500°C to 650°C for 6h to 10h, performing shaping and grading treatment again, and then reacting it at 2400°C to 3000°C for 36h to 72h for high-temperature graphitization treatment, and finally obtaining an unmodified artificial graphite material after grading treatment; then further dissolving the unmodified artificial graphite material and asphalt in a dispersant, stirring to obtain a uniform mixed liquid, passing the uniform mixed liquid through a closed-cycle spray dryer to prepare a composite powder, and then heating it at 700°C to 1100°C for 1h to 5h, and finally obtaining the asphalt liquid-phase coated modified artificial graphite material. The asphalt liquid-phase coated modified artificial graphite prepared by this method exhibits excellent electrochemical properties such as high charge and discharge efficiency, high specific capacity, and good cycle performance after being applied to lithium batteries.

[0003] Although the existing liquid phase coating technology has shown certain performance advantages, there are still problems such as poor uniformity of asphalt or petroleum coating and easy agglomeration after coating. At the same time, asphalt and other substances are easy to harm human health, the heating temperature of the coating kettle is basically >900℃, the energy consumption is too high, and there are many uncontrollable factors. Summary of the invention

[0004] In view of the problems in the prior art such as poor uniformity after liquid phase coating, easy agglomeration after coating and the possibility of asphalt and the like being harmful to health, high heating temperature of the coating kettle resulting in high energy consumption and many uncontrollable factors, the present invention provides a step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials. The novel preparation method has the advantages of controllable growth, good coating density and uniformity. The obtained graphite negative electrode material has good cycle stability, especially the cycle capacity at low temperature (0°C) is greatly improved.

[0005] In order to achieve the above object, the present invention provides the following technical solutions: The first object of the present invention is to provide a step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials, comprising the following specific steps: S1. Preparation of the core layer of graphite negative electrode material: selecting a graphite base material, and obtaining an artificial graphite negative electrode material through crushing, coating, carbonization, graphitization, and screening; S2. Preparation of carbon-coated graphite composite negative electrode material: Place the graphite negative electrode material obtained in S1 in a tubular furnace or a fluidized bed CVD furnace, introduce inert gas to exhaust the air in advance, evacuate the temperature and raise the temperature to 650°C to 750°C, first introduce a small amount of carbon source gas to carry out the nucleation reaction of the amorphous carbon layer, then introduce inert gas to exhaust the remaining carbon source gas, then introduce a certain amount of carbon source gas to carry out the growth reaction of the amorphous carbon layer, and then introduce inert gas and carbon source gas in turn to carry out the growth reaction, and after 2 to 6 cycles, a graphite composite negative electrode material is obtained.

[0006] After the graphite substrate material is prepared, the preparation method of the present invention adopts a step-by-step CVD method to carry out carbon coating deposition growth. At the same time, in each step, by controlling the type, flow rate, temperature, pressure and other conditions of the reaction gas, the gas phase precursor is gradually chemically reacted and deposited on the surface of the substrate material to form a coating layer. The main principle is: after a reaction gas is introduced, it is adsorbed and reacted on the surface of the graphite material to generate an initial thin film, which can change the active sites on the surface of the material. At the same time, since the reaction is slow and is a nucleation reaction, the film has the advantages of high density and high uniformity. When the film is used as a substrate for subsequent film growth, the subsequent film can also achieve the characteristics of high density and high uniformity. After multiple cycles of growth, the material has good density and uniformity, thereby greatly improving the stability of the material, and then improving the cycle stability of the battery material.

[0007] Furthermore, in the above technical solution S1, the graphite base material is green coke or calcined coke; a 325-mesh sieve is used for screening, and after screening, the graphite negative electrode material is baked at 120° C. to 180° C. for 10 h to 12 h.

[0008] Furthermore, in the above technical solution S2, the inert gas is any one or more of nitrogen, argon, and helium, and the flow rate is 0.5L / min to 20L / min.

[0009] Furthermore, in the above technical solution S2, the carbon source gas is any one of methane, acetylene, ethylene, and propylene; and after vacuuming, a slight negative pressure of 0.8 MPa to 0.9 MPa is maintained.

[0010] Furthermore, in the above technical solution S2, the flow rate of the carbon source gas in the nucleation reaction is 0.1L / min to 1L / min, preferably 0.1L / min to 0.3L / min; the single reaction time is 1min to 30min, preferably 2min to 5min.

[0011] Furthermore, in the above technical solution S2, the flow rate of the carbon source gas in the growth reaction is 0.5L / min to 2L / min, preferably 0.5L / min to 1L / min; the single reaction time is 2min to 60min, preferably 10min to 30min.

[0012] Furthermore, in the above technical solution S2, the number of cycles is 4 to 6 times; and the carbon coating amount is 0.5% to 2% of the total amount of the graphite negative electrode material.

[0013] The second object of the present invention is to provide a graphite composite negative electrode material prepared by the above preparation method, wherein the graphite composite negative electrode material is used in a lithium battery and has a remaining capacity of more than 87.5% after 500 cycles at 0°C.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses a graphite substrate as the core layer of the negative electrode material, and then adopts a step-by-step CVD method to first deposit an initial thin film on the surface of the core layer at a low speed for nucleation reaction to obtain a coating film with high density and uniformity, and then grows amorphous carbon layers layer by layer at a relatively higher speed. The cyclic growth reaction steps can greatly improve the density and uniformity of the carbon coating layer. The distributed CVD preparation method has the characteristics of controllable growth and uniform and dense coating, which greatly improves the cycle stability of the material, especially the cycle stability at low temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 This is a scanning electron microscope image of the graphite composite negative electrode material in Example 2 of the present invention; Figure 2 This is a scanning electron microscope image of the graphite composite negative electrode material in Comparative Example 1 of the present invention; Figure 3 This is a scanning electron microscope image of the graphite core material in Comparative Example 3 of the present invention; Figure 4 A comparison chart of capacity decay curves at room temperature after the negative electrode materials obtained in various embodiments of the present invention and comparative examples are assembled into lithium batteries; Figure 5 A comparison chart of capacity attenuation curves at 0° C. after the negative electrode materials obtained in each embodiment of the present invention and comparative examples 1 to 2 are assembled into lithium batteries; Figure 6 This is a capacity decay curve at 0°C after the negative electrode material obtained in Comparative Example 3 of the present invention is assembled into a lithium battery. DETAILED DESCRIPTION

[0017] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials involved in the following examples are common commercial products and can be purchased from the market unless otherwise specified.

[0018] The above-mentioned technical features of the present invention and the technical features specifically described below (such as embodiments) can be combined with each other to form a new or preferred technical solution.

[0019] The raw materials involved in the embodiments of the present invention are either existing commercially available products or can be prepared according to existing methods, and the testing methods are industry methods.

[0020] Example 1 A step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials comprises the following specific steps: S1. Preparation of the core layer of graphite negative electrode material: select raw coke or calcined coke as the graphite base material, and obtain artificial graphite negative electrode material through crushing, coating, carbonization, graphitization and screening. Then, after passing through a 325-mesh sieve, bake at 120° C. for 12 hours to remove moisture, and dry for use; S2. Preparation of carbon-coated graphite composite negative electrode material: 5 kg of graphite negative electrode material obtained in S1 is placed in a tubular furnace or a fluidized bed CVD furnace, and nitrogen is introduced at a flow rate of 10 L / min for 30 minutes in advance to evacuate the air in the furnace body. After the furnace is evacuated, a slight negative pressure of 0.8 MPa to 0.9 MPa is maintained, and the temperature is raised to 750°C. Methane gas is first introduced at a flow rate of 0.2 L / min for nucleation reaction of the amorphous carbon layer, and the reaction is carried out for 5 minutes. Then, nitrogen is introduced at a flow rate of 8 L / min for 15 minutes to evacuate the remaining carbon source gas, and then methane gas is introduced at a flow rate of 1.0 L / min for growth reaction of the amorphous carbon layer, and the reaction is carried out for 60 minutes. Subsequently, inert gas and carbon source gas are introduced in sequence for growth reaction. After four cycles, an amorphous carbon-coated graphite composite negative electrode material is obtained.

[0021] Example 2 A step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials comprises the following specific steps: S1. Preparation of the core layer of graphite negative electrode material: select raw coke or calcined coke as the graphite base material, and obtain artificial graphite negative electrode material through crushing, coating, carbonization, graphitization and screening. Then, after passing through a 325-mesh sieve, bake at 150° C. for 11 hours to remove moisture, and dry for standby use; S2. Preparation of carbon-coated graphite composite negative electrode material: 5 kg of the graphite negative electrode material obtained in S1 is placed in a tubular furnace or a fluidized bed CVD furnace, and nitrogen is introduced at a flow rate of 10 L / min for 30 minutes in advance to evacuate the air in the furnace body. After the furnace is evacuated, a slight negative pressure of 0.8 MPa to 0.9 MPa is maintained, and the temperature is raised to 700°C. Acetylene carbon source gas is first introduced at a rate of 0.1 L / min to carry out the nucleation reaction of the amorphous carbon layer, and the reaction is carried out for 3 minutes. Then, nitrogen is introduced at a flow rate of 8 L / min for 15 minutes to evacuate the remaining carbon source gas, and then acetylene gas is introduced at a flow rate of 0.8 L / min to carry out the growth reaction of the amorphous carbon layer, and the reaction is carried out for 20 minutes. Subsequently, an inert gas and a carbon source gas are introduced in sequence for the growth reaction. After 6 cycles, an amorphous carbon-coated graphite composite negative electrode material is obtained.

[0022] Example 3 A step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials comprises the following specific steps: S1. Preparation of the core layer of graphite negative electrode material: select raw coke or calcined coke as the graphite base material, and obtain artificial graphite negative electrode material through crushing, coating, carbonization, graphitization and screening. Then, after passing through a 325-mesh sieve, bake at 180° C. for 10 h to remove moisture, and dry for use; S2. Preparation of carbon-coated graphite composite negative electrode material: 5 kg of graphite negative electrode material obtained in S1 is placed in a tubular furnace or a fluidized bed CVD furnace, and nitrogen is introduced at a flow rate of 10 L / min for 30 minutes in advance to evacuate the air in the furnace body. After the furnace is evacuated, a slight negative pressure of 0.8 MPa to 0.9 MPa is maintained, and the temperature is raised to 650°C. Ethylene carbon source gas is first introduced at a rate of 0.15 L / min to carry out the nucleation reaction of the amorphous carbon layer, and the reaction is carried out for 5 minutes. Then, nitrogen is introduced at a rate of 8 L / min for 15 minutes to evacuate the remaining carbon source gas, and then ethylene gas is introduced at a rate of 1.0 L / min to carry out the growth reaction of the amorphous carbon layer, and the reaction is carried out for 20 minutes. Subsequently, inert gas and carbon source gas are introduced in sequence for growth reaction. After 6 cycles, an amorphous carbon-coated graphite composite negative electrode material is obtained.

[0023] Comparative Example 1 A method for preparing a graphite composite negative electrode material, which differs from Example 2 in that, in S2, a step-by-step CVD method is not used for preparation, but a one-time deposition is performed, the furnace temperature is raised to 700°C, 1.0L / min acetylene gas is introduced for a vapor deposition reaction, and the reaction time is 2h to obtain a graphite composite negative electrode material.

[0024] Comparative Example 2 A method for preparing a graphite composite negative electrode material, which differs from Example 3 in that in S2, a step-by-step CVD method is not used for preparation, but a one-time deposition is performed, the furnace temperature is raised to 650°C, 1.0L / min ethylene gas is introduced for a vapor deposition reaction, and the reaction time is 2h to obtain a graphite composite negative electrode material.

[0025] Comparative Example 3 A method for preparing a graphite composite negative electrode material is different from that of Example 2 in that, in S2, the CVD method is not used for preparation, but a graphitized core material is directly used as the graphite composite negative electrode material.

[0026] Test example 1. Compare the electron microscope images of the graphite composite negative electrode materials prepared in Example 2 and Comparative Example 1. Figure 1 This is a scanning electron microscope image of the graphite composite negative electrode material obtained in Example 2. Figure 2 This is a scanning electron microscope image of the graphite composite negative electrode material obtained in Comparative Example 1. It can be seen that the particle morphology in Example 2 is more regular and dispersed, the surface is more uniform and dense, and its lattice fringes are clearer and the crystal defects are slightly less.

[0027] 2. The graphite negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were assembled into lithium batteries and then subjected to performance tests. The results are shown in Table 2, wherein the performance test conditions of Table 1 are shown in Table 1.

[0028] Table 1 Performance test conditions

[0029] Table 2 Comparison of buckle performance

[0030] From the results in Table 2, it can be seen that the carbon layer coating of graphite negative electrode material by the step-by-step CVD method of the present invention has little effect on the capacity and initial efficiency of graphite, but it greatly improves the cycle of the battery, especially the cycle capacity at low temperature; at the same time, compared with the one-step CVD method, the cycle performance of the negative electrode material prepared by the step-by-step CVD method is further improved because the amorphous carbon layer is more compact. From the capacity decay curve comparison diagram ( Figures 4 to 6 ) It can also be seen that the graphite composite negative electrode material obtained by the present invention has better cycle performance, especially the graphite composite negative electrode material obtained in Example 2 still has a capacity residual rate of 90.5% after 500 cycles at low temperature (0°C), and has good low-temperature cycle stability; while the capacity of graphite directly used as the negative electrode material is only 48.9% after 80 cycles at 0°C, and has poor low-temperature cyclability.

[0031] In summary, the present invention uses a graphite substrate as the core layer of the negative electrode material, and then adopts a step-by-step CVD method to first perform a nucleation reaction at a low speed to deposit a layer of high-density and uniform initial film, and then cyclically grows layers of amorphous carbon layers at a relatively higher speed, which can greatly improve the density and uniformity of the carbon coating layer. The distributed CVD preparation method has the characteristics of controllable growth and uniform and dense coating, which can effectively improve the cycle stability of lithium batteries, especially the cycle stability of lithium batteries at low temperatures.

[0032] Finally, it should be emphasized that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials, characterized in that: The specific steps include: S1. Preparation of the core layer of graphite negative electrode material: selecting a graphite base material, and obtaining an artificial graphite negative electrode material through crushing, coating, carbonization, graphitization, and screening; S2. Preparation of carbon-coated graphite composite negative electrode material: Place the graphite negative electrode material obtained in S1 in a tubular furnace or a fluidized bed CVD furnace, introduce inert gas to exhaust the air in advance, evacuate the temperature and raise the temperature to 650°C to 750°C, first introduce a small amount of carbon source gas to carry out the nucleation reaction of the amorphous carbon layer, then introduce inert gas to exhaust the remaining carbon source gas, then introduce a certain amount of carbon source gas to carry out the growth reaction of the amorphous carbon layer, and then introduce inert gas and carbon source gas in turn to carry out the growth reaction, and after 2 to 6 cycles, a graphite composite negative electrode material is obtained.

2. The step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials according to claim 1, characterized in that: In S1, the graphite base material is green coke or calcined coke; a 325-mesh screen is used for screening, and after screening, the graphite negative electrode material is baked at 120° C. to 180° C. for 10 h to 12 h.

3. The step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials according to claim 1, characterized in that: In S2, the inert gas is any one or more of nitrogen, argon and helium, and the flow rate is 0.5L / min to 20L / min.

4. The step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials according to claim 1, characterized in that: In S2, the carbon source gas is any one of methane, acetylene, ethylene and propylene; after vacuuming, a slight negative pressure of 0.8 MPa to 0.9 MPa is maintained.

5. The step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials according to claim 1, characterized in that: In S2, the flow rate of the carbon source gas in the nucleation reaction is 0.1 L / min to 1 L / min, and the primary reaction time is 1 to 30 min.

6. The step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials according to claim 5, characterized in that: The flow rate of the carbon source gas in the nucleation reaction is 0.1L / min to 0.3L / min, and the reaction time is 2min to 5min.

7. The step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials according to claim 1, characterized in that: In S2, the flow rate of the carbon source gas in the growth reaction is 0.5 L / min to 2 L / min, and the single reaction time is 2 min to 60 min.

8. The step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials according to claim 7, characterized in that: The flow rate of the carbon source gas in the growth reaction is 0.5L / min to 1L / min, and the time for one reaction is 10min to 30min.

9. The step-by-step CVD preparation method for improving the low-temperature cyclability of graphite negative electrode materials according to claim 1, characterized in that: In S2, the number of cycles is 4 to 6 times; the carbon coating amount is 0.5% to 2% of the total amount of the graphite negative electrode material.

10. A graphite composite negative electrode material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The graphite composite negative electrode material is used in a lithium battery and has a capacity remaining of more than 87.5% after 500 cycles at 0°C.

Citation Information

Patent Citations

  • Preparation method of asphalt liquid phase coated modified artificial graphite lithium battery cathode material

    CN103682350B

  • Production process of high-capacity liquid-phase coating agent

    CN118619267A

  • A Si / C layered anode active material used for lithium batteries and a preparing method thereof

    CN107749470A

  • Regenerated graphite material and preparation method thereof

    CN111439748A

  • Low-temperature fast-charging artificial graphite negative electrode material, preparation method and low-temperature fast-charging battery

    CN113851614A